1990
DOI: 10.1139/y90-106
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature on contractile mechanisms of rainbow trout (Salmo gairdneri) intestine

Abstract: Experiments were designed to determine whether contractility of trout smooth muscle in vitro varied with temperature and if changes occurred at the receptor or intracellular levels. The role of calcium in contractility at various temperatures was also investigated. Isolated trout intestinal segments, approximately 2 cm in length, were suspended isometrically under 2 g tension in 10-mL organ baths containing trout Ringer's solution aerated with O2 and CO2 (95:5). Contractions of trout intestine were not statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The effects of temperature are likely directed at the enzymatic mechanisms involved in smooth muscle contraction since most metabolic processes are temperature dependent over a specific range (Sizer 1943;Prosser 1991). However, receptor properties of smooth muscle, including the function of voltage-operated calcium channels, can be affected by temperature changes (Cook et al 1977;Wolowyk et al 1987;Burka et al 1990). Changes in receptors in rainbow trout intestinal smooth muscle appear to occur when a rapid temperature change is applied to tissue in vitro (Burka et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effects of temperature are likely directed at the enzymatic mechanisms involved in smooth muscle contraction since most metabolic processes are temperature dependent over a specific range (Sizer 1943;Prosser 1991). However, receptor properties of smooth muscle, including the function of voltage-operated calcium channels, can be affected by temperature changes (Cook et al 1977;Wolowyk et al 1987;Burka et al 1990). Changes in receptors in rainbow trout intestinal smooth muscle appear to occur when a rapid temperature change is applied to tissue in vitro (Burka et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, receptor properties of smooth muscle, including the function of voltage-operated calcium channels, can be affected by temperature changes (Cook et al 1977;Wolowyk et al 1987;Burka et al 1990). Changes in receptors in rainbow trout intestinal smooth muscle appear to occur when a rapid temperature change is applied to tissue in vitro (Burka et al 1990). Some of these effects can also be attributed to intracellular contractile mechanisms (Burka et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cited studies utilized fish which had been temperature acclimated (4-20°C) for 6 to 8 weeks prior to experimentation. The contractility of rainbow trout gastrointestinal smooth muscle in vitro also depends on temperature (Burka et al 1990(Burka et al , 1993. Those studies showed a marked linear increase in efficacy and a slight increase in potency to the smooth muscle contractile agonists, 5-hydroxytryptamine (5-HT; serotonin) and carbachol, the depolarizing agent, KCI, and transmural electrical stimulation (TMS) of the muscle with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%